Corruption and Human Rights in the Case Law of Inter-American Human Rights Treaty Bodies - Lis, Edyta (Review of European and Comparative Law, 2022)
The first attempts to combat corruption date back to ancient times and had mainly moral connotation. Despite being an old phenomena, nowadays it takes new shapes and becomes a more common feature of social life, especially in the Latin America region. Corruption is a complex, and multidimensional phenomenon that negatively impacts human rights on many levels. Therefore, serious effort have long been made at global, regional and state levels to combat corruption. The United Nations and regional organizations have adopted numerous non-binding and binding documents with a view to stifling this phenomenon but none of them refer to the issue of impact of corruption on human rights. But it should be stressed that it is very hard to establish a link between corruption and human rights violations. Some efforts has been made by the Inter-American Court of Human Rights (IACHR) and the Inter-American Commission on Human Rights (IAComHR). This article considers whether and how the IACHR and the IAComHR establish the link between corruption and violation of human rights in the inter-American system. It also determines which groups of people are, according the IACHR and the IAComHR, particularly affected by corruption, what measures should be taken to protect those exposed to acts of corruption, what obligations are incumbent on States with a view to preventing, combating and eradicating corruption.